2013
DOI: 10.1002/hec.2961
|View full text |Cite
|
Sign up to set email alerts
|

What Roles Do Contemporaneous and Cumulative Incomes Play in the Income-Child Health Gradient for Young Children? Evidence From an Australian Panel

Abstract: The literature to date shows that children from poorer households tend to have worse health than their peers, and the gap between them grows with age. We investigate whether and how health shocks (as measured by the onset of chronic conditions) contribute to the income-child health gradient and whether the contemporaneous or cumulative effects of income play important mitigating roles. We exploit a rich panel dataset with three panel waves called the Longitudinal Study of Australian children. Given the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
(97 reference statements)
0
18
0
Order By: Relevance
“…This paper examines the impact of maternal mental health on child health, relating to a very large body of literature on intergenerational transmissions in various aspects such as income or education (Solon, 1999;Black and Devereux, 2011). It also relates to a rich body of literature on the impact of parental income on child health (Case et al, 2002;Apouey and Geoffard, 2013;Fletcher and Wolfe, 2014;Khanam et al, 2014;Kuehnle, 2014), as well as emerging literature on the effects of parental health on child education (Bratti and Mendola, 2014;Alam, 2015;Le and Nguyen, 2015). 1 However, this paper more closely connects to an emerging body of research focusing on the relationship between parental health and child health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This paper examines the impact of maternal mental health on child health, relating to a very large body of literature on intergenerational transmissions in various aspects such as income or education (Solon, 1999;Black and Devereux, 2011). It also relates to a rich body of literature on the impact of parental income on child health (Case et al, 2002;Apouey and Geoffard, 2013;Fletcher and Wolfe, 2014;Khanam et al, 2014;Kuehnle, 2014), as well as emerging literature on the effects of parental health on child education (Bratti and Mendola, 2014;Alam, 2015;Le and Nguyen, 2015). 1 However, this paper more closely connects to an emerging body of research focusing on the relationship between parental health and child health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of these studies found a positive relationship between socioeconomic effect and child health [10, 11, 18, 29, 30]. The most common variable used as a proxy for socioeconomic status of the household in recent past has been maternal educational status [2, 9, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…In this section, I investigate the relationship between reported (subjective) children's health status and total household income using the conditional likelihood estimator that uses all (J − 1) T transformations. The analysis in this section follows that in Murasko (2008) and Khanam et al (2014). 21 In an influential paper, Case, Lubotsky, and Paxson (2002) use pooled cross-section data from the United States to document that reported children's health is positively related to household income.…”
Section: Empirical Illustrationmentioning
confidence: 99%
“…However, they find that magnitude of the relationship is much smaller than that reported in Case et al (2002), and they do not find evidence that the strength of the relationship increases with the age of the child. Khanam et al (2014) use Australian data. This study appears to be the first that controls for time-invariant unobserved heterogeneity in this literature.…”
Section: Empirical Illustrationmentioning
confidence: 99%